Current Status of Antimicrobial Drug Use in Japanese Companion Animal Clinics and the Factors Associated With Their Use - Makita, Kohei; Sugahara, Nami; Nakamura, Kazuhiro; Matsuoka, Takeshi; Sakai, Masato; Tamura, Yutaka (Frontiers in Veterinary Science, 2021)
The Japanese National Action Plan on Antimicrobial Resistance (AMR) was adopted to strengthen AMR surveillance and monitoring in companion animals. The Japanese Veterinary Antimicrobial Resistance Monitoring (JVARM) system monitors the sale of veterinary antimicrobial drugs by pharmaceutical companies, and the sale of human drugs by principal wholesale companies to companion animal (dogs and cats) clinics. However, the data do not include sales by local drug suppliers and personal importation to companion animal clinics in Japan. The purposes of this study were to estimate total antimicrobial drug use by companion animal clinics in Japan and to identify the factors associated with their use. In 2018, questionnaires gathering data on attributes of the clinic and volumes of antimicrobial drugs used were sent to 212 clinics across Japan by the Japan Veterinary Medical Association. Out of the clinics, 170 valid questionnaires were returned (80.2% response rate). Antimicrobial drugs were categorized first as human, veterinary, or imported drugs and then further categorized as important drugs (critically important drugs for humans and second-choice veterinary drugs) or others. Total antimicrobial drug use was estimated based on the number of clinics reported in 2016. The relationships between antimicrobial drug use and various questionnaire items were analyzed using non-parametric regression analysis. Total antimicrobial drug use was estimated at 29.9t, which was 2.1 times higher than reported by the JVARM survey on the sales of antimicrobial drugs. In terms of total use, important drugs and human drugs accounted for 12.6% and 61.8%, respectively. Clinic income per veterinarian was associated with total antimicrobial use per veterinarian. The proportion of important drugs among all antimicrobial drugs used in a clinic was high in recently established clinics with middle-aged and older directors.